Nitridation of high speed steel by electron cyclotron resonance plasma - Majeed, Riyadh M A Abdul; Purohit, Vishwas; Bhide, Rajesh; Mandale, A. B.; Bhoraskar, S. V.; Bhoraskar, Vasant N. (Journal of Physics D-Applied Physics, 2006)
Plasma nitridation of high speed M2 steel is studied using a microwave assisted electron cyclotron resonance plasma source. A mixture of hydrogen and nitrogen with a proportion of 7 : 3 was used as the nitriding gas. The density of plasma for this forming gas was measured to be similar to 10(18) m(-3) as estimated by a double probe method. The M2 steel was nitrided at various temperatures of 400, 450, 500 and 550 degrees C under similar reactor conditions. The nitrided layer was characterized by using various analytical techniques which included structural, morphological, chemical and microhardness measurement. The maximum thickness of the nitrided layer was found to be 48 mu m for samples nitrided at 550 degrees C. No layer corresponding to white/compound layer is seen in our analysis. The hardness is seen to increase from similar to 580HV to similar to 1190HV for samples nitrided at 550 degrees C. Electron cyclotron resonance plasma nitridation is observed to be much faster and a cleaner process as compared with the conventional nitriding process.